국내 영어 교육 분야에서의 비판적 사고 관련 연구 동향 - 방준(Bang, Jyun) (영어교과교육, 2019)
The purpose of this study was to analyze the trends on critical thinking studies of English education in domestic. For this, 43 papers related to critical thinking of English education for 19 years from 2000 to 2018 were collected from RISS, KISS, DBPIA, NDSL, National Library of Korea, National Assembly Library, National Digital Library. The papers were analyzed according to six standards such as the date of research, publication type, subject, research methodology, research theme and purpose of study. The key-words extracted from the abstract were analyzed by utilizing key-word network analysis methods namely NetMiner. The results showed that the studies on critical thinking of English education have increased steadily centered around university students. In the early 2000’s, studies that focused on ‘critical thinking’ and ‘critical reading’ were developed in various ways such as ‘writing, speaking’ and ‘discussion.’ In the key-word network analysis, ‘critical thinking’ as centered key-word frequency, and key-words ‘critical literacy,’ ‘critical reading,’ ‘critical pedagogy,’ ‘college student’ and ‘writing class’ were the primary key-words. Based on these results, it was suggested that more research on critical thinking of English education reflecting more various age groups and language skills be necessary. KCI Citation Count: 0